1996
DOI: 10.1016/0014-5793(96)00701-6
|View full text |Cite
|
Sign up to set email alerts
|

Differences in DNA‐binding efficiency of Sp1 to aldolase and pyruvate kinase promoter correlate with altered redox states in resting and proliferating rat thymocytes

Abstract: Thymocytes induce their glycolytie enzymes as they undergo transition from the resting to the proliferating state. Corresponding increases in mRNA levels point to a transcriptional regulation. Electrophoretic mobility shift assays revealed that the DNA-binding efficiency of Spl is increased when nuclear extracts from proliferating compared to resting rat thymocytes were used. Here we demonstrate that hydrogen peroxide, added to nuclear extract from proliferating cells, decreases the Spl DNA-binding activity, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

1997
1997
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…Sp1 stimulates cAMPdependent transcriptional stimulation from the CYP11A gene promoter in SL2 cells (52). However, it has been reported that the phosphorylated and the nonreduced form of Sp1 showed a decrease in binding to a DNA fragment that contained both GC boxes 1 and 2 of the PKM gene (51,53). On the other hand, cdc25C gene transcription, which occurs late in the S/G 2 phase, is regulated by a cell cycle-dependent repressor element and an upstream activating sequences which contains three CCAAT motifs and two Sp1-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Sp1 stimulates cAMPdependent transcriptional stimulation from the CYP11A gene promoter in SL2 cells (52). However, it has been reported that the phosphorylated and the nonreduced form of Sp1 showed a decrease in binding to a DNA fragment that contained both GC boxes 1 and 2 of the PKM gene (51,53). On the other hand, cdc25C gene transcription, which occurs late in the S/G 2 phase, is regulated by a cell cycle-dependent repressor element and an upstream activating sequences which contains three CCAAT motifs and two Sp1-binding sites.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, chemiluminescence measurements revealed that resting, but not proliferating thymocytes do produce peroxide anions. This could be the reason for the observed decrease in Spi-binding efficiency with nuclear extracts from resting thymocytes [5].…”
Section: Introductionmentioning
confidence: 99%
“…Previous experiments [5] with nuclear extracts from prolif- erating rat thymocytes revealed that hydrogen peroxide decreases the binding activity of Spi to the aldolase A and pyruvate kinase M 2 promoters. Addition of DTE fully restores DNA binding efficiency.…”
Section: Influence Of Oxidative Stress Onmentioning
confidence: 99%
See 2 more Smart Citations